Analisis Konsekuensi Ekonomi Akibat Kejahatan di Indonesia - Palokoto, Tarina; Purwanti, Evi Yulia; Mudakir, Y. Bagio (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
Crime affects people’s decisions in carrying out economic activity. This study aims to analyze the influence of several crime typologies and non-crime variables on per capita Gross Regional Domestic Product (GRDP) and identify the existence of spatial dependencies of per capita GRDP in Indonesia. The study used cross section data with the Spatial Lag Model (SLM). The results show that there is a negative spatial autocorrelation in per capita GRDP. Murder and labor affect GRDP per capita negatively. Meanwhile, fraud, embezzlement, and corruption; local government expenditure, life expectancy, domestic investment, and foreign investment affect per capita GRDP positively per capita GRDP.